Pleomorphic adenomas of the parotid: removal without rupture. - Hancock, B. D. (Royal College of Surgeons of England, 1987)
A personal series of 64 new pleomorphic adenomas of the parotid were removed with a very low rate of capsular rupture (1.6%) using a flexible approach. The aim was to remove the tumour with a covering of normal parotid where possible after exposing the trunk and appropriate branches of the facial nerve. Exposure of the capsule, however, was unavoidable in some situations, as in deep tumours, those in contact with the nerve and in very superficial tumours. Great care must be taken to avoid capsular rupture and, provided this is done, long term recurrence rates of less than 2% can be expected.